Combining proteomics and bioinformatics to explore novel tegumental antigens as vaccine candidates against Echinococcus granulosus infection - Miles, Sebastián; Portela, Madelón; Cyrklaff, Marek; Ancarola, María Eugenia; Frischknecht, Friedrich; Durán, Rosario; Dematteis, Sylvia; Mourglia‐Ettlin, Gustavo (Journal of cellular biochemistry, 2019)
Echinococcus granulosus is the parasite responsible for cystic echinococcosis (CE), an important worldwide-distributed zoonosis. New effective vaccines against CE could potentially have great economic and health benefits. Here, we describe an innovative vaccine design scheme starting from an antigenic fraction enriched in tegumental antigens from the protoscolex stage (termed PSEx) already known to induce protection against CE. We first used mass spectrometry to characterize the protein composition of PSEx followed by Gene Ontology analysis to study the potential Biological Processes, Molecular Functions, and Cellular Localizations of the identified proteins. Following, antigenicity predictions and determination of conservancy degree against other organisms were determined. Thus, nine novel proteins were identified as potential vaccine candidates. Furthermore, linear B cell epitopes free of posttranslational modifications were predicted in the whole PSEx proteome through colocalization of in silico predicted epitopes within peptide fragments identified by matrix-assisted laser desorption/ionization-TOF/TOF. Resulting peptides were termed “clean linear B cell epitopes,” and through BLASTp scanning against all nonhelminth proteins, those with 100% identity against any other protein were discarded. Then, the secondary structure was predicted for peptides and their corresponding proteins. Peptides with highly similar secondary structure respect to their parental protein were selected, and those potentially toxic and/or allergenic were discarded. Finally, the selected clean linear B cell epitopes were mapped within their corresponding 3D-modeled protein to analyze their possible antibody accessibilities, resulting in 14 putative peptide vaccine candidates. We propose nine novel proteins and 14 peptides to be further tested as vaccine candidates against CE.